Osteoclastogenesis markers in craniofacial bone defects after demineralized dentin material membrane implantation as guided bone regeneration - Dedy Agoes Mahendra; Anita Yuliati; Masfueh Razali; Noor Hayaty Abu Kasim; Muhammad Alwino Bayu Firdauzy; Retno Indrawati Roestamadji; Pratiwi Soesilawati (Journal of Applied Oral Science)
Abstract Guided bone regeneration (GBR) is an alternative treatment for craniofacial bone defects reconstruction through membrane barrier adaptation, such as demineralized dentin material membrane (DDMM). DDMM is used as a substitute for GBR material, which aligns with Green Economy principles, it has a good biological osteoinductive and osteoconductive effects, and its structure resembles bones. The balance of bone remodeling when experiencing craniofacial defects will be altered and allow changes to resorption activity, so the mechanisms of osteoclastogenesis and bone resorption are vital. Objective: this article aims to analyze the expression of TNF-α, RANKL, and osteoclast cells count after application of DDMM as GBR in mandibular bone defects. Methodology: this is an experimental study with a post-test only control group design, which began with the randomization of 120 rats into five groups: K(−), without membrane implantation; K(+), PPCM; P1, DDMM; P2, DDMM + bone graft; P3, PPCM + bone graft. The expression of TNF-α, RANKL, and osteoclast cells count were observed, followed by analysis using a one-way ANOVA and post hoc Tukey HSD comparison test. Results: there were significant differences in the expression of TNF-α, RANKL, and osteoclast cells count in all study groups (p=0.000). TNF-α showed a decreasing difference with the highest expression in the K(−) group on day 3 of 12.00±2.16. RANKL expression increased on day 14 and decreased on day 21 in all groups. The osteoclast cells count generally showed a critical period with the highest increase in the K(−) group on day 14 of 73.00±0.00. Conclusion: DDMM has the potential to be a superior membrane substitute compared to PPCM as GBR in alternative treatment for craniofacial bone defects reconstruction.